Plasma‐activated Ringer's lactate solution inhibits the cellular respiratory system in HeLa cells. Issue 10 (26th July 2021) - Tanaka, Hiromasa; Maeda, Shogo; Nakamura, Kae; Hashizume, Hiroshi; Ishikawa, Kenji; Ito, Mikako; Ohno, Kinji; Mizuno, Masaaki; Motooka, Yashiro; Okazaki, Yasumasa; Toyokuni, Shinya; Kajiyama, Hiroaki; et al.
Abstract: Nonequilibrium atmospheric pressure plasma has enabled a variety of new applications in medicine, agriculture, and other industries. It is particularly noteworthy that plasma itself and/or plasma‐activated culture medium have been shown to preferentially kill various cancer cells. We have previously developed a plasma‐activated Ringer's lactate solution (PAL) for use as a new cancer treatment. In this study, behaviors of extracellular and intracellular reactive oxygen and nitrogen species in the cellular respiratory system of PAL‐treated HeLa cells were investigated using an extracellular flux analyzer and a probe to measure mitochondrial membrane potential. In PAL‐treated HeLa cells, extracellular hydrogen peroxide in PAL was found to be responsible for the induction of intracellular hydrogen peroxide and apoptosis, while other components in PAL are responsible for the induction of non‐H2 O2 intracellular ROS and non‐apoptotic cell death, which should be clarified by further experiments. We believe that these are long‐lived species derived from plasma‐activated lactates. Furthermore, we found that the plasma‐activated lactates inhibited glycolysis and the tricarboxylic acid (TCA) cycle, but not the electron transport chain in HeLa cells. These results suggest that PAL induces multiple modes of cell death, including apoptosis through hydrogen peroxide, and non‐apoptotic cell death associated with the impairment of mitochondrial functions (glycolysis and TCA cycle). These findings shed light on the novel mechanism underlying plasma‐activated lactate‐induced cell death. Abstract : Plasma‐activated Ringer's lactate solution (PAL) inhibits glycolysis and the tricarboxylic acid (TCA) cycle in HeLa cells. Extracellular H2 O2 induces intracellular H2 O2 by penetrating through aquaporins, subsequently inducing apoptosis in HeLa cells. Non‐H2 O2 PAL components in PAL (PAL2w) induce intracellular ROS (but not H2 O2 ), which are responsible for the impairment of the mitochondrial respiratory system, glycolysis, and the TCA cycle, ultimately inducing non‐apoptotic cell death in HeLa cells. The arrowheads represent stimulatory relationships and the blunt arrowheads represent inhibitory relationships